Balanced Scorecard: Is It Beneficial Enough? A Literature Review - Ratnaningrum, .; Aryani, Y. Anni; Setiawan, Doddy (Asian Journal of Accounting Perspectives, 2020)
Purpose of the Research: This study reviews and evaluates the development of research on the balanced scorecard. Design/ Methodology/ Approach: This is a literature study of71 articles from 21 Scopus Q1 indexed journals. The issuance year was ignored, yet the search area was restricted to business, management, and accounting. The analysis is grouped into three parts, namely BSC in private sectors, BSC in public sectors, and criticism for BSC. In private sectors and SMEs, the theme is divided into benefits of BSC, implementations of BSC, limitations and other tools to improve BSC. Research finding: Although a large number of academics are sceptical about the relationship between BSC and organisational outcomes, BSC is widely used. Practitioner-oriented literature shows that it has useful values especially in improving organisational performance and strategy attainment. Based on the findings of empirical results in the private sector, SMEs, and the public sector, it can be inferred that the implementation status of the balanced scorecard shows a high level of success and minimal failure. Theoretical contribution/ Originality: The BSC has limitations, yet these findings show that BSC is beneficial enough. Practitioner/ Policy implication: The BSC remains worth considering for a performance management system. Limitation/ Implication: This literature review is limited to specific quality ratings of the academic journals. Type of article: Literature review Keywords: Balanced Scorecard, Kaplan and Norton, Management Accounting, Literature Review JEL Classification: M21, M41